(untitled) (Research, Society and Development, 2022)
Obesity is a high prevalence condition worldwide, and bariatric surgery is the most effective long-term treatment. Half these surgeries are performed in women of potentially fertile ages, but it is yet not clear what are the outcomes of having a pregnancy in this postoperative period. Accordingly, an integrative review was performed to approach maternal obesity and their implications on the health of the maternal-fetal binomial. Accordingly, an integrative review was performed on Pubmed from march to May 2021 to raise data about Post-bariatric pregnancy. 424 articles dated between 2010 and 2020 were found using the keywords “Pregnancy”, “Bariatric Surgery” and “outcome”. 13 publications dated between 2010 and 2020 were analyzed. The year 2020 had the highest publication prevalence, with a total of 4 (30,79%) articles. Considering the different techniques used to perform bariatric surgery, it was concluded that the malabsorptive procedure has the highest chance of complicating, especially by having a small gestational age fetus. Furthermore, assessing the interval between surgery and conception, no consensus was found. Therefore, there is need for multi-professional orientation for post-bariatric pregnant women and adequate vitamin supplementation, which is related to better pregnancy outcomes and lower rates of fetal malformation.